Juridical Analysis Of The Settlement Of Defaulted Debtors With Fiduciary Guarantees At PT Mitra Gadai Kepri In Batam City - Tonny Tonny; Ali Amran; Tartib Tartib; Erniyanti Erniyanti; Soerya Respationo (International Journal of Sociology and Law, 2024)
PT Mitra Gadai Kepri is one of the Private Pawnshops in Batam City which is licensed by OJK to provide financing products. However, the business of financing activities carried out often occurs Default, especially with Fiduciary Guarantees. Based on the description in this thesis, the problems to be studied are: 1)How is the Legal Arrangement Related to the Settlement of Default Debtors with Fiduciary Guarantees at PT Mitra Gadai Kepri in Batam City. 2)How is the Implementation Related to the Settlement of Debtor Default with Fiduciary Guarantee at PT Mitra Gadai Kepri Partner in Batam City. 3)What Factors are the Obstacles / Constraints and Solutions Related to the Settlement of Default Debtors with Fiduciary Guarantees at PT Mitra Gadai Kepri in Batam City. The method in this research is Normative Legal research supported by empirical research. Therefore, the Legislation and Conceptual approach will be carried out. Used in data collection in this research with Interviews and Literature Studie. The results of the study concluded that consumers who default with fiduciary guarantees due to low understanding of financial literacy. As well as not knowing the existence of regulations governing the protection of consumers and the public in the Financial Services Sector in resolving defaults with fiduciary guarantees. Suggestions in this study are that the OJK and Financial Services Business Actors must increase Financial Literacy and Inclusion in the wider community and include the government in eradicating illegal financial services. Financial Services Business Actors must analyze the ability to pay prospective customers in order to minimize defaults, especially with fiduciary guarantees and must resolve defaults in accordance with applicable regulations. And an appeal to the public to be wiser and more selective in choosing financial service products and institutions that provide these services.